Collaborative Governance Dalam Pengelolaan Sampah Melalui Program Salin Swara Di Kota Bontang - Jeanne Steza Ryna Sianturi; Kus Indarto (Jurnal Inovasi dan Kreativitas (JIKa), 2024)
Problems: The volume of waste accumulation in Bontang City increases every year. Therefore PT. Badak LNG initiated the Salin Swara Program in collaboration with the Bontang City Environmental Service and the community which focuses on waste banks. From the observation results, problems were identified that there is still a lack of commitment from the parties in collaboration, there are not yet adequate waste processing facilities, there is a lack of human resources, there are no formal collaboration benchmarks related to targets, and there are still sectoral egos. Purpose: Describe and analyze collaborative governance in waste management through the Salin Swara Program in Bontang City as well as the driving and inhibiting factors in the collaboration process. Methodology: This research uses descriptive research methods with a qualitative approach. Data collection techniques in this research were carried out by observation, interviews, documentation. Interactive model data analysis techniques. Results/Findings: The research results show that the collaboration carried out through the Salin Swara Program in Bontang City is not optimal. There are still shortcomings in four aspects of government collaboration, such as, in terms of institutional design, mutually agreed performance standards in collaboration have not been developed. In terms of the collaboration process, it shows that there is still a lack of intensity of face-to-face dialogue carried out by each party. Lack of commitment from the community, there has not been a mutual understanding between the parties regarding the objectives of the collaboration. Paper Type: Descriptive Keywords: Collaborative Governance, Waste, Program, Salin Swara